Biorefinery approach and environment-friendly extraction for sustainable production of astaxanthin from marine wastes. (19th May 2019) - Routray, Winny; Dave, Deepika; Cheema, Sukhinder K.; Ramakrishnan, Vegneshwaran V.; Pohling, Julia
Abstract: Microorganisms (microalgae and fungi) are currently the main sources of astaxanthin; however, this carotenoid also accumulates in crustaceans, salmonids, and birds. Seafood (derived from marine animals) processing wastes are significant sources of astaxanthin and can be employed as feed and for nutraceutical applications, where shrimp wastes are the most exploited seafood industry waste employed for astaxanthin extraction. This review discusses different sources, efficient environment-friendly extraction methods employed for astaxanthin extraction, biorefinery approaches for efficient extraction and future aspects of the application of these waste sources for commercial preparation of astaxanthin complexes. It also includes a brief overview of the advantages, disadvantages, and challenges for obtaining astaxanthin from various sources and various case scenarios integrating different biorefinery approaches.